Pemodelan Arima Intervensi untuk Meramalkan Jumlah Kendaraan Masuk Melalui Tol Pasteur Tahun 2014-2023 - Winda Aya Haliza; Nusar Hajarisman (UNISBA Press, 2024)
Abstract. Intervention modeling analysis is a time series data analysis model used toforecast data containing interventions or unexpected events from both internal andexternal factors. In general, there are two types of functions in intervention analysis,namely step and pulse. During the Covid-19 pandemic, various policies implementedby the government, one of which is PPKM. Based on the time series data patternof[ the number of vehicles entering through the Pasteur Toll Road, it can be seen thatthere was a significant decrease when the PPKM policy was implemented due to theCovid-19 pandemic. The data used in this study is data on the number of vehiclesentering through the Pasteur Toll gate in the period January 1, 2014 to December 31,2023. The purpose of this study is to assess the effect of the PPKM policy interventiondue to the emergence of the Covid-19 pandemic in Indonesia on the number ofvehicles entering through the Pasteur Toll Road. The results of this study indicate thatthe ARIMA modeling for forecasting the number of vehicles, considering theintervention, is best represented by the ARIMA (0,0,1) model with an interventionorder of (b = 1, r = 3, s = 0), which shows that the intervention effect occurred oneperiod, or one month since the intervention event with a negative influence, leadingto a notable decrease in the number of vehicles entering through the Pasteur Toll Roadover the 2014-2023 period. Abstrak. Analisis pemodelan intervensi adalah suatu model analisis data deret waktuyang digunakan untuk meramalkan data yang mengandung intervensi atau kejadianyang tidak terduga baik dari faktor internal maupun eksternal. Secara umum, terdapatdua jenis fungsi pada analisis intervensi yaitu step dan pulse. Selama pandemi Covid-19, terdapat kebijakan yang diterapkan pemerintah salah satunya adalah PPKM.Berdasarkan pola data deret waktu jumlah kendaraan yang masuk melalui Tol Pasteurterlihat bahwa terdapat penurunan yang signifikan pada saat diterapkan kebijakanPPKM karena pandemi Covid-19. Data yang digunakan dalam penelitian ini adalahdata jumlah kendaraan masuk melalui gerbang Tol Pasteur pada periode 1 Januari2014 sampai dengan 31 Desember 2023. Tujuan dari penelitian ini adalah untukmelihat pengaruh intervensi adanya kebijakan PPKM karena munculnya pandemiCovid-19 di Indonesia pada jumlah kendaraan yang masuk melalui Tol Pasteur. Hasildari penelitian ini adalah didapat bahwa pemodelan ARIMA intervensi untukmeramalkan jumlah kendaraan yang masuk melalui Tol Pasteur adalah modelARIMA (0,0,1) dengan orde intervensi (b=1,r=3,s=0) yang menunjukkan bahwaadanya efek intervensi terjadi satu periode atau 1 bulan sejak terjadinya kejadianintervensi dengan pengaruh negatif yaitu penurunan pada jumlah kendaraan yangmasuk melalui Tol Pasteur pada data tahun 2014-2023.